Renal Replacement Therapy - Shigematsu, Takashi
Renal Replacement Therapy is a peer-reviewed journal facilitating worldwide discussion of research and issues related to the study of renal replacement therapy. RRT considers articles on all aspects of hemodialysis, peritoneal dialysis, blood purification, renal transplantation and regenerative medicine. In addition, the journal publishes content in wider fields such as chronic kidney disease (CKD), acute kidney injury (AKI), critical care medicine and intensive care, bone and mineral metabolism, anemia and iron metabolism, infection, cardiac disease, cerebral disease, diabetes mellitus, hypertension, nutrition, and related social issues. Contributions are encouraged from a global perspective across many disciplines.